Two new frog species from the Litoria rubella species group from eastern Australia - Rowley, J. J. L.; Mahony, M. J.; Hines, H. B.; Myers, S.; Price, L.c.; Shea, G.m.; Donnellan, S. C. (Zootaxa, 2021)
The bleating tree frog (Litoria dentata) is one of the more prominent pelodryadid frogs of eastern Australia by virtue of its extremely loud, piercing, male advertisement call. A member of the Litoria rubella species group, L. dentata has a broad latitudinal distribution and is widespread from coastal and subcoastal lowlands through to montane areas. A recent mitochondrial DNA analysis showed a deep phylogeographic break between populations of L. dentata on the mid-north coast of New South Wales. Here we extended the mitochondrial survey with more geographically comprehensive sampling and tested the systematic implications of our findings with nuclear genome wide single-nucleotide polymorphism, morphological and male advertisement call datasets. While similar in appearance and in male advertisement call, our integrative analysis demonstrates the presence of three species which replace each other in a north-south series. We redescribe Litoria dentata, which is restricted to coastal north-eastern New South Wales, and formally describe Litoria balatus sp. nov., from south-eastern Queensland, and Litoria quiritatus sp. nov., from the mid-coast of New South Wales to north-eastern Victoria.